Clinical Characteristics of Necrotizing Enterocolitis Diagnosed by Independent Adjudication of Abdominal Radiographs, Laparotomy, or Autopsy in Preterm Infants in the “Connection Trial” - Neu, Josef; Singh, Rachana; Demetrian, Mihaela; Flores-Torres, Jaime; Hudak, Mark; Zupancic, John A.; Kronström, Anders; Rastad, Jonas; Strömberg, Staffan; Thuresson, Marcus; The “Connection Study” Group (American Journal of Perinatology, 2024)
Objective Necrotizing enterocolitis (NEC) classically is diagnosed by radiographic demonstration of pneumatosis intestinalis/portal venous gas (PI/PVG). This study examines clinical characteristics of NEC confirmed by independent evaluation of abdominal radiographs, taken for clinical signs of NEC, or by pathologic findings at laparotomy or autopsy (confirmed NEC [cNEC]).Study Design The investigated cohort included 1,382 extremely low birth weight (BW) infants (BW range: 500–1,000 g) with median 27 weeks (range: 23–32) gestational age (GA) at birth. They were randomized into the placebo-controlled “Connection Trial” of the new biological drug candidate IBP-9414 with cNEC as one primary endpoint.Results Total 119 infants (8.6%) had cNEC diagnosed at median 14 days of age by confirming PI/PVG at X-ray adjudication (n = 111) and/or by surgery/autopsy (n = 21). Sixteen percent of cNEC cases died. Adverse events of NEC were reported in 8.5% of infants and 4.1% had NEC diagnosed by radiology and surgery/autopsy at the participating centers. Regression analyses showed that the risk of cNEC decreased by 11 to 30% for every 100-g increment in BW and single-week increment in GA and associated cNEC with odds ratios (ORs) > 2.0 for gastrointestinal (GI) perforation and obstruction, hypotension, hypokalemia, hypophosphatemia, and death. Comparing risks of cNEC in infants below and above 750-g BW showed higher ORs (2.7–4.3) for GI perforation, hypotension, hypokalemia, and renal complications in the smaller infants, whereas the bigger infants had higher ORs (1.9–3.2) for serious non-GI events, late-onset sepsis (LOS), and death. Predictors of cNEC (hazard ratio, HR > 1.5) included serious non-GI events (mainly infections), hyponatremia, and hyperglycemia, whereas the HR was 0.52 for intravenous antibiotics. After cNEC diagnosis, there were higher rates of GI perforation and obstruction, hypotension, hypokalemia, and LOS.Conclusion Independent adjudication of abdominal radiographs increased radiological recognition of NEC and proved to be feasible in a multicenter study setting as well as able to diagnose clinically relevant NEC.Key Points
Keywords: ELBW infants; abdominal radiography; necrotizing enterocolitis; clinical associations; risk factors